The Effect of Glycerol on the Properties of Biodegradable Cassava Starch (Saai Dieow Cultivar) Films for Plastic Plant Bag Application - theamdee, Pawinee; Pansaeng, Natchanan (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 4 (2019): October-December 2019DO - 10.14456/nujst.2019.34, 2019)
This paper reports the effect of glycerol on the properties of biodegradable cassava starch films for plastic plant bag application. The film was prepared by dissolving cassava starch in water to the concentration of 5 wt%. To study the effect of the glycerol content on these properties, the amount of glycerol (plasticizer) was added during the formulation varied from 0 to 45 %w/w (0, 15, 25, 35 and 45 %w/w). The films were cast in a mold and dried at 60 o C for 24 h. The thickness of the films was in the range of 0.10-0.21 mm. The a w (water activity) of films ranged from 0.40 to 0.53. The water solubility, water vapor permeability and softness of the film increased with the increasing of glycerol content. The percent elongation of the starch films increased with the decrease of the glycerol content and, in contrast, the tensile and puncture strength decreased. After the films were buried under the ground (8-10 cm depth) for 3 weeks, they were degraded by 100%. Degree of the degradation increased with the increasing of glycerol content. The biodegradable film plant bags were used to the transplanting of marigold seedlings production period (6 weeks). The cassava starch film with 35 wt% glycerol showed the best overall properties. These results indicated that cassava starch biodegradable film could be used for plastic plant bag application. In addition, this made-of-natural film is biodegradable, which can help to reduce the amount of non-biodegradable packaging waste.     Keywords: cassava starch, glycerol, plasticizer, biodegradable film